A robust approach to the two-level humanitarian relief operation. (2017) - Qu, Yaping
During the initial disaster response phase, an important issue in humanitarian relief logistics is to tackle the complexity of decision-making that covers the appropriate relief allocation and the associated transportation plan. We propose a two-level modelling methodology to alleviate that challenge, where the upper-level model focuses on the strategic relief distribution policy among the recipients whereas the lower-level model deals with the transportation routes, vehicle deployment and loading problems at the operational level based on the upper-level solution. Furthermore, in view of the demand uncertainty in impacted areas, a robust model is developed to guarantee the feasibility of relief distribution solutions. Also, a case study is conducted to illustrate the benefit of the presented robust framework, which is not only favourable in terms of the reliability and equity level relative to the deterministic one but also capable of offering advice on the vehicle arrangement.